US Instability: Challenges for Inbound Student and Faculty Mobility - Altbach, Philip; Wan, Xiaofeng; de Wit, Hans (International Higher Education, 2023)
The United States is seen by many around the world as a significantly unstable society with an uncertain future. Trumpism, safety concerns, racism, and politicization of US higher education are the main concerns. This perception, based largely on reality, has, and will continue to have, implications for US higher education attractiveness and relations with the rest of the world.